Exercise training ameliorates myocardial phenotypes in heart failure with preserved ejection fraction by changing N6-methyladenosine modification in mice model - Liu, Kai; Ju, Wenhao; Ouyang, Shengrong; Liu, Zhuo; He, Feng; hao, Jingyi; Guan, Hongyan; Wu, Jianxin (Frontiers in Cell and Developmental Biology, 2022)
Heart failure with preserved ejection fraction (HFpEF) shows complicated and not clearly defined etiology and pathogenesis. Although no pharmacotherapeutics have improved the survival rate in HFpEF, exercise training has become an efficient intervention to improve functional outcomes . Here, we investigated N6-methyladenosine (m6A) RNA methylation modification in a “two-hit” mouse model with HFpEF and HFpEF with exercise (HFpEF + EXT). The manner of m6A in HFpEF and HFpEF + EXT hearts were explored via m6A-specific methylated RNA immunoprecipitation followed by high-throughput and RNA sequencing methods. A total amount of 3 992 novel m6A peaks were spotted in HFpEF+EXT, and 426 differently methylated sites, including 371 hypermethylated and 55 hypomethylated m6A sites, were singled out for further analysis (fold change >2, p < 0.05). According to gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, unique m6A-modified transcripts in HFpEF+EXT were associated with apoptosis-related pathway and myocardial energy metabolism .HFpEF+EXT had higher total m6A levels and downregulated fat mass and obesity-related (FTO) protein levels. Overexpression of FTO cancels out the benefits of exercise in HFpEF+EXT mice by promoting myocyte apoptosis, myocardial fibrosis and myocyte hypertrophy. Totally, m6A which is a significant alternation of epitranscriptomic processes, is a potentially meaningful therapeutic target.